Análisis jurídico de la etapa de juzgamiento en el proceso penal contra adolescentes infractores en la ciudad de Machala, provincia de El Oro, durante el periodo comprendido al año 201. Propuesta de reformas jurídicas. - Rodríguez Meneses, Carlos Luis (2013)
For the realization of this legal research, we focus specifically on the study of organic code of childhood and adolescence, Book IV, Chapter II, text in which is established the process by which juvenile offenders are judged and his rights during that period of time. This legal research seeks to find a real structure under Ecuadorian law, preferably in the issue of prosecution of juvenile offenders, their relationship with the Constitution of the Republic of Ecuador, international treaties and conventions and the Law, where are guaranteed, compliance and exercise all the rights of adolescents adapt their behavior to a criminal and who are called to trial for alleged responsibility.